Study of Viral Photoinactivation by UV-C Light and Photosensitizer Using a Pseudotyped Model - Mohammad Sadraeian; Fabio Francisco Pinto Junior; Marcela Miranda; Juliana Galinskas; Rafaela Sachetto Fernandes; Edgar Ferreira da Cruz; Libing Fu; Le Zhang; Ricardo Sobhie Diaz; Gustavo Cabral-Miranda; Francisco Eduardo Gontijo Guimarães (MDPI AG, 2022)
Different light-based strategies have been investigated to inactivate viruses. Herein, we developed an HIV-based pseudotyped model of SARS-CoV-2 (SC2) to study the mechanisms of virus inactivation by using two different strategies; photoinactivation (PI) by UV-C light and photodynamic inactivation (PDI) by Photodithazine photosensitizer (PDZ). We used two pseudoviral particles harboring the Luciferase-IRES-ZsGreen reporter gene with either a SC2 spike on the membrane or without a spike as a naked control pseudovirus. The mechanism of viral inactivation by UV-C and PDZ-based PDI were studied via biochemical characterizations and quantitative PCR on four levels; free-cell viral damage; viral cell entry; DNA integration; and expression of reporter genes. Both UV-C and PDZ treatments could destroy single stranded RNA (ssRNA) and the spike protein of the virus, with different ratios. However, the virus was still capable of binding and entering into the HEK 293T cells expressing angiotensin-converting enzyme 2 (ACE-2). A dose-dependent manner of UV-C irradiation mostly damages the ssRNA, while PDZ-based PDI mostly destroys the spike and viral membrane in concentration and dose-dependent manners. We observed that the cells infected by the virus and treated with either UV-C or PDZ-based PDI could not express the luciferase reporter gene, signifying the viral inactivation, despite the presence of RNA and DNA intact genes.